2018
DOI: 10.1111/asj.13094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary coated‐oleum cinnamomi supplementation on the immunity and intestinal integrity of broiler chickens

Abstract: Oleum cinnamomi (OCM) is increasingly used as a feed additive in animal diets. The aim of this study was to investigate the effects of dietary supplementation with coated-OCM (cOCM) on the immunity and intestinal integrity of broiler chickens. A total of 396 one-day-old chicks were randomly assigned into six groups. The basal diets were supplemented with 50 mg/kg of flavomycin (positive control) as well as 0 (control), 50, 100, 200, and 300 mg/kg of cOCM. Compared with the control, both positive control and cO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In this study, the Anti G+ and Anti G− bacterial communities were not able to promote the improvement of intestinal villus height and crypt depth, which departs from previous studies’ results. Other studies have shown that the whole long-term feeding of flavomycin can increase villus height [15] or have no effect [24]. The Anti G+ group built in the first 5 days did not change the intestinal shape.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, the Anti G+ and Anti G− bacterial communities were not able to promote the improvement of intestinal villus height and crypt depth, which departs from previous studies’ results. Other studies have shown that the whole long-term feeding of flavomycin can increase villus height [15] or have no effect [24]. The Anti G+ group built in the first 5 days did not change the intestinal shape.…”
Section: Discussionmentioning
confidence: 90%
“…Total RNA isolation and quantitative real-time polymerase chain reaction (qRT-PCR) was conducted as described by Guo et al [17]. Briefly, total RNA of hepatic and cardiac samples was isolated using TRIzol Reagent protocol (Invitrogen, Carlsbad, CA, USA).…”
Section: Rna Isolation and Quantitative Real-time Polymerase Chain Rementioning
confidence: 99%
“…Moreover, apart from a positive influence on intestinal morphology in some aspects, PFA supplementation was sometimes associated with a decrease in villous height in the supplemented groups 49 , 144 , 145 . Dietary supplementation of chicken broilers with cOCM was associated with improved intestinal integrity manifested by villus development and modulation of the gene expression of TJ proteins and MUC-2, but no improvement in the birdsʼ growth performance was observed 144 . This is consistent with the results of PFA supplementation (commercial phytogenic product Digestarom) obtained by Ahsan et al, where there was no difference among the dietary treatments for growth performance and cecal microbe populations at any phase 12 .…”
Section: Gut Health and The Intestinal Barriermentioning
confidence: 96%
“…The more the epithelium is exposed to various harmful factors, the greater the depth of the crypts. The positive effect of PFAs (a combination of carvacrol, cinnamaldehyde, and Capsicum oleoresin, piperine, genistein and hesperidin, oregano EO, lavender powder, a combination of CUR, carvacrol, thymol and cinnamaldehyde, cOCM) on gut morphology includes reduced CD 15 , 24 , 31 , 35 , 42 , 49 , 144 , 145 , which can be interpreted as limited exposure to various stressors, lesser inflammatory response, and sloughing. The cell turnover is also an energy consuming process and shallow crypts suggest that the bird can spare nutrients for growth 12 .…”
Section: Gut Health and The Intestinal Barriermentioning
confidence: 99%
See 1 more Smart Citation